Traumatic Maculopathy (Berlin´S Edema) Treated with Enhancement of Human Photosynthesis® - Solís Herrera, Arturo; del Carmen Arias Esparza, María; Eugenia Solís Arias, Paola (Journal of Aging Research And Healthcare, 2025)
Commotio retinae (CR) is a condition frequently observed in clinical practice, particularly following closed globe trauma (CGT) due to sport, labor, or traffic accident injuries. It is the main cause of unilateral vision loss in male patients aged between. It is characterized by transient gray-white retinal coloration and reduction of visual acuity (VA). Symptoms depend mainly on the location and severity (deep) of the injury, with less complains when only the superficial or peripheral retina is affected. It may be confined to the posterior pole, when it is also called Berlin’s edema, after the first hypothesis of Berlin (1873). There is no specific treatment since the treatment depends on the region of the retina and choroid affected. In this work we report a case of Berlin edema, treated with ǪIAPI 1®, to restore the balance of oxygen, which is generated at the intracellular level.
Keywords: Berlin´s edema; blunt ocular trauma; choroid rupture; commotio retinae; subretinal hemorrhage